The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
+8 votes
1.6k views

Four fair coins are tossed simultaneously. The probability that at least one head and one tail turn up is

  1. $\frac{1}{16}$
  2. $\frac{1}{8}$
  3. $\frac{7}{8}$
  4. $\frac{15}{16}$
asked in Probability by Veteran (59.4k points) | 1.6k views
+2

Total outcomes - 24  (Because 4 coins are tossed simultaneously and each coin has 2 outcomes-either head or tail)
Now out of this 16 outcomes, one will be all HHHH(all heads) and other will be all TTTT(all tails) rest 14 outcomes will have atleast one head and one tail.

So, probability, favourable events/total outcome

14/16 = 7/8

4 Answers

+15 votes
Best answer

Answer - C

probability of getting all heads =$\dfrac{1}{16}$

probability of getting all tails =$\dfrac{1}{16}$

probability of getting at least one head and one tail $= 1 - \dfrac{1}{16} - \dfrac{1}{16} = \dfrac{7}{8}.$

answered by Loyal (9k points)
edited by
+10 votes

Total outcomes - 24  (Because 4 coins are tossed simultaneously and each coin has 2 outcomes-either head or tail)
Now out of this 16 outcomes, one will be all HHHH(all heads) and other will be all TTTT(all tails) rest 14 outcomes will have atleast one head and one tail.

So, probability, favourable events/total outcome

14/16 = 7/8

answered by Loyal (8.8k points)
–1 vote
1 head 3 tails =1/16 2 heads 2 tails =1/16 3 heads 1 tail =1/16 adding we get 3/16 where i am wrong anyone plz explain
answered by Boss (14.1k points)
+7

1 head 3 tails =1/16 * 4C1 = 1/4

2 heads 2 tails =1/16 *4C2 = 3/8

3 heads 1 tail =1/16 *4C3 = 1/4

So, adding gives 7/8. 

 

–1 vote
probability of getting head=p=1/2;

by the formula p(x)=nCx*P^xq^(n-x)

p(atleast one tail)=p(x>=1)==1-p(x<1)=4C0*(1/2)^4=1-1/16=15/16

p(atleast one head)=p(x>=1)==1-p(x<1)=4C0*(1/2)^4=1-1/16=15/16

so

P(head&tail)=15/16*15/16=7/8
answered by (81 points)
+2
number of probabilities of 4 coins = 2⁴ = 16

We have a formula that
         P(x≥1)+P(y≥1)

               = 1-(P(x<1)+P(y<1))

               = 1-(P(x=0)+P(y=0))

               = 1-((1/16)+(1/16))
               = 1-(2/16)
               = 7/8


Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true

36,171 questions
43,624 answers
124,025 comments
42,893 users